The Re-Establischment of Lithuanian Customs and the Regulation of Movement of the Goods Through National Border - Tamulevičius, Jonas (Ekonomika, 1999)
In this work the issues of the re-establishment of lithuanian customs, of the documents regulating its activity and the regulation of the movement of goods through national border, which heavily depends on the economic state of the country, are analysed. To the opinion of the author, the legal framework of the activity of customs was created till the middle of 1991. It has been developed further to suit better the changing economic conditions of the country and need to be worked on even more as a part of the process of preparation of Lithuania for joining EU. The process involves the work on customs procedures, the declaration forms, the creation of unified informational system, the evaluation of goods crossing the border, the improvement of customs infrastructure, the establishment of additional customs posts and improvement of their activities. The next issues considered in the work is the necessity of the diminishment of the role of non tariff barriers and the role of the state institutions in the customs price setting.